ANALISIS PENGGUNAAN FORWARD CONTRACT DAN OPTION PADA PERUSAHAAN EKSPOR UD DAMENA DI DENPASAR - Lubis, Gita Syeba; Rahyuda, Henny (E-Jurnal Manajemen; Vol 7 No 4 (2018)DO - 10.24843/EJMUNUD.2018.v07.i04.p18, 2018)
The export company receives income in foreign currency so it will be affected by the exchange rate risk. The purpose of this research is to know the application of hedging forward contract and option method in UD Damena (Seafood Supply & Processing Product) in 2014-2016. This research is quantitative descriptive. The research object used is the resultt of forward contract and option usage which is seen from the increase of foreign exchange differences from export transaction receivables obtained by UD Damena (Seafood Supply & Processing Product) in year 2014-2016. Data collection methods is non-behavioral observation by collecting data from written sources. Data analysis techniques using descriptive techniques by describing the phases of forward contract and option systematically. The results concluded that forward contract and option minimize the risk of exchange rate by generating greater exchange rate difference and option resulted in a lager exchange rate increase than the forward contract.   Keyword: exchange rate risk, hedging, forward contract, option.